Concise assembly of 7-ethynyl-6, 8-dioxabicyclo[3.2.1]octanes from acetylenes and ketones. Issue 15 (27th March 2023) - Schmidt, Elena Yu.; Bidusenko, Ivan A.; Protsuk, Nadezhda I.; Ushakov, Igor A.; Trofimov, Boris A.
Abstract : A new family of natural-related bicyclic ketals became readily accessible in a simple atom-economic two-step procedure from acetylenes and ketones under mild transition-metal-free conditions. Abstract : 2-Acetyl-3, 4-dihydropyrans, assembled from acetylene gas and ketones in a one-pot procedure, are ethynylated with acetylenes (KOBu t /DMSO, 15 °C, 2 h) to give acetylenic alcohols, which readily cyclize (TFA, rt, 5 min) to 7-ethynyl-6, 8-dioxabicyclo[3.2.1]octanes in up to 92% yield. The ring closure of the above acetylenic alcohols can be performed without their isolation from the reaction mixture. Thus, the synthesis of 7-ethynyl-6, 8-dioxabicyclo[3.2.1]octanes can be realized in just two synthetic operations from simple and available starting materials under mild transition-metal-free conditions.